Identification of valuable compounds from the shell of the edible oyster Crassostrea gigas - Bonnard, Michel (HAL CCSD, 2020)
This thesis program was carried out in a partnership between the oyster farming company Tarbouriech-Médithau, located on the edge of the Thau lagoon (Marseillan), and two institutes of The Balard Chemistry Centre of The University of Montpellier: The Institute of Biomolecules Max Mousseron and The Institute Charles Gerhart Montpellier. The main objective was the identification of valuable compounds from the shells of the oyster Crassostrea gigas Tarbouriech-Médithau with singular morphological and organoleptic properties. This study was positioned within the more general framework of the recycling of the shell of this edible oyster as a source of natural materials, highlighting the advantages and challenges related to its recycling as well as the need to participate to the investigation particular fundamental aspects not described to date.Thus, the pink-purple colour of the shell of the oyster Crassostrea gigas was investigated in order to extract and identify the biomolecules contributing to this colour. The extraction required the development of original and reliable methods, applicable to the extraction of acid-soluble pigments. The structural investigation of these compounds conducted by reverse phase liquid chromatography combined with high-resolution mass spectrometry, by fluorescence spectroscopy and by nuclear magnetic resonance, made possible the newly identification of heterocyclic biomolecules such as porphyrins. The extraction and the identification of these compounds open the way to applications and allow to consider the development of innovative recycling processes of shells of the oyster Crassostrea gigas. Ces travaux de thèse ont été réalisés dans le cadre d’une convention industrielle de formation par la recherche (Cifre) entre l'entreprise ostréicole Tarbouriech-Médithau, basée à Marseillan sur le bord de l’Etang de Thau, et deux instituts du Pôle Chimie Balard de l’Université de Montpellier : l'Institut des Biomolécules Max Mousseron et l'Institut Charles Gerhart Montpellier. L’objectif ...